External Cyclicality in the Face of Aggregate Demand Shocks: Pros and Cons Across Developed and Developing Countries. (2nd May 2018) - Kandil, Magda
Abstract : The paper studies variation in the effects of aggregate demand shocks on the external sector and underlying components and distinguishes between the effects of expansionary and contractionary shocks. The aim is to study the determinants and implications of cyclicality across advanced and developing countries. The composite evidence points to high degree of cyclicality in many countries. Based on time‐series correlations, there is a stronger cyclical co‐movement between the trade and current account balances across advanced countries, compared to developing countries. Further, fluctuations in the financial balance are dependent on developments in exports in many developing countries. The determinants of external vulnerability vary with macroeconomic indicators. The evidence points to higher vulnerability of the external balance with respect to higher trend inflation across developing countries. In addition, constraints on capacity in developing countries could risk external stability as trend growth increases across countries. Government spending is an important determinant of external stability in developing countries, reflecting the adverse implications of higher government spending and a widening fiscal deficit on debt sustainability and external financial flows. Further, private consumption is a key driver of aggregate uncertainty and cyclical fluctuations in the external balances across developing countries.